(untitled) (Mediscope, 2015)
The objective of the study was to find out the incidence of abnormal cardiotocography (CTG) findings in pregnancies at risk, to find out the suitable time of delivery of the fetus at risk and to find out the fetal outcome in abnormal antepartum CTG findings. It is a prospective study where 450 highrisk pregnancy cases of different gestational age, ranging from 32-42 weeks were selected from BSMMU, Dhaka and Khalishpur Clinic, Khulna from 2003 to 2013. CTG was done on admission and the subjects were followed-up till delivery. The data obtained from the present study were compiled and appropriate statistical analysis was carried out using SPSS. Out of the cases, normal CTG was found in 357 cases and abnormal CTG was found in 93 cases. Among these 93 cases, normal outcome was found in 87 cases (93.1%) and abnormal outcome in 6 cases (6.9%). The specificity, sensitivity, negative predictive value and positive predictive value for antepartum CTG was 92.5%, 20.5%, 81.9% and 49.3%, respectively. This study revealed that CTG shows more accuracy in case of healthy fetus that a normal CTG almost always gave a normal fetal outcome. But if CTG showed abnormality, the fetal outcome may be normal. So a more accurate correlation with other biophysical and biochemical parameters of fetus is to be done for further evaluation. DOI: http://dx.doi.org/10.3329/mediscope.v1i1.21632 Mediscope Vol. 1, No. 1: 2014, Pages 19-22